ҚАЗАҚСТАН ХАЛҚЫНЫҢ СЕМІЗДІККЕ ШАЛДЫҒУЫНА ƏСЕР ЕТЕТІН ФАКТОРЛАРҒА АНАЛИЗ (Experimental biology, 2009)
In experiments on mice it was shown that the fraction КФ:F1 of the extracellular metabolite of Fusarium solani fungus suppressed temperately the growth and development of Erlich solid carcinoma and had no effect upon the growth and development of Luis solid carcinoma
Keywords: Erlich solid; fraction КФ